Réponses

2013-10-05T11:43:33+02:00
A=(x-5)(2x+1)-5
= x * 2x + x * 1 + (-5) * 2x + (-5) * 1 - 5
= 2x + 1x + (-10x) + (-5) - 5
= 3x - 10x - 10
= -7x - 10

B=(1+x)-(2x+3) au carré
= 2 * 2x + 1 * 3 + x * 2x + x * 3 au carré
= 4x + 3 + 2x + 3x au carré
= 9x + 3 au carré
= 81x + 9

C=(3x+2)au carré -(x-4) au carré
= 3x * x + 3x * (-4) + 2 * x + 2 * (-4)
= 3x + (-12x) + 2x + (-8)
= -7x - 8
2013-10-05T11:44:05+02:00
A = (x-5)(2x+1)-5
A = (x+2x + x*1) * (-5+2*x + (-5)+1) -5
A = (2x(au carré) + 1x ) * -10x -6 -5
A= (2x(au carré) +1x) * -10x-1

Chui pas sûre que cest sa mais voila ta une ptite idée